The Postmodern Significance of Max Weber's Legacy. - Koshul, Basit Bilal (Palgrave Macmillan, 2006)
One of Max Weber's contemporaries described him as 'a child of the Enlightenment born too late' whose work is a 'vitriolic attack on religion'. Subsequent Weber scholarship has largely affirmed this valuation of Weber and characterized his scholarship as a manifestation of the very disenchantment that Weber describes. In The Postmodern Significance of Max Weber's Legacy, Basit Koshul challenges this idea by showing Weber to be a postmodern thinker far ahead of his time.